Feasibility of employing thick microbeams from superficial and orthovoltage kVp x-ray tubes for radiotherapy of superficial cancers. (November 2017) - Kamali-Zonouzi, P.; Shutt, A.; Nisbet, A.; Bradley, D.A.
Abstract: Preclinical investigations of thick microbeams show these to be feasible for use in radiotherapeutic dose delivery. To create the beams we access a radiotherapy x-ray tube that is familiarly used within a conventional clinical environment, coupling this with beam-defining grids. Beam characterisation, both single and in the form of arrays, has been by use of both MCNP simulation and direct Gafchromic EBT film dosimetry. As a first step in defining optimal exit-beam profiles over a range of beam energies, simulation has been made of the x-ray tube and numbers of beam-defining parallel geometry grids, the latter being made to vary in thickness, slit separation and material composition. For a grid positioned after the treatment applicator, and of similar design to those used in the first part of the study, MCNP simulation and Gafchromic EBT film were then applied in examining the resultant radiation profiles. MCNP simulations and direct dosimetry both show useful thick microbeams to be produced from the x-ray tube, with peak-to-valley dose ratios (PVDRs) in the approximate range 8.8–13.9. Although the potential to create thick microbeams using radiotherapy x-ray tubes and a grid has been demonstrated, Microbeam Radiation Therapy (MRT) would still need to be approved outside of the preclinical setting, a viable treatment technique of clinical interest needing to benefit for instance from substantially improved x-ray tube dose rates. Highlights: Thick microbeam radiation therapy shows potential for clinical introduction. MCNP simulation and Gafchromic film demonstrate the creation of thick microbeams using clinical radiotherapy x-ray tubes. The microbeams provide the PVDRs desired for MRT.